Cantonese media promotes Chinese cultural identification: structural equation modeling based on Malaysian Chinese - Liu, Nian; Chen, Tongyu; Peng, Yuqing; Xie, Ying (Frontiers in Psychology, 2023)
Language media from one’s hometown is an important means of maintaining cultural identification, especially for minorities. Cantonese media plays an active role in shaping the Chinese cultural identification of ethnic Chinese all over the world. To date, few researchers have undertaken quantitative empirical analyses of the mechanism through which Cantonese media influences cultural identification. Using data from 642 Malaysian Chinese, this study established a structural equation model with the partial least squares method. We found that the emotional affinity of ethnic Chinese to Cantonese media can influence identification with Chinese culture through the perceived value of Cantonese media and cognition of Chinese culture. The perceived value of Cantonese media (IE = .208) and cognition of Chinese culture (IE = .068) play partial mediation roles. Meanwhile, emotional affinity to Cantonese media influences cognition of Chinese culture (IE = .069) through the chain mediation of perceived value of Cantonese media and cognition of Chinese culture. Age has a partial moderating effect in the structural equation model. Compared with minors, adults’ emotional affinity to Cantonese media can eventually influence identification with Chinese culture (TEdiff = .126) more strongly through several mediation paths. The study suggests a need to cultivate the emotional affinity of ethnic Chinese to Cantonese media, improve the multidimensional values of Cantonese media, and endow Cantonese media with functions of cultural dialogue and knowledge transmission. The international transmission of Cantonese media could play a vital role in building a cultural community for ethnic Chinese globally.